Hepatitis B and C amongst the OPD patients Seeking Dental Treatment at Khyber College of Dentistry Peshawar - Walid Khan, Rozina Shahadat Khan, Abid Ullah, Muhammad Shah, Naveed Ahmad, Murad Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatitis is an inflammatory condition of the liver; mostly caused by hepatitis B virus (HBV) and hepatitis C virus. These viruses are the main cause of severe liver disease as well as Hepatocellular carcinoma and liver cirrhosis. Hepatitis B is preventable through vaccination which is not possible in case of Hepatitis C. Aim: To access magnitude of hepatitis B and C amongst OPD patients seeking dental treatment at Khyber College of Dentistry Peshawar. Methods: Cross sectional study was conducted at KCD Peshawar. A total 13270 samples were collected during the period of March 2019 to June 2019 selected through Consecutive sampling technique. All the patients were screened for HBS, HCV by ICT method before any dental procedure. Those samples which were found positive for HBS and HCV were reconfirmed by ELISA technique Results: The total percentages of negative HBV were 13110(98.8%) while HBV positive diagnosed patients were 160(1.2%). While Total HCV positive were 233(1.8%) among these males were 143(1.6%) while females were 90(2.0%) Conclusion: Study has shown HCV which has poor prognosis comparative to HBV is more prevalent demanding more health education interventional programs by planning and policy makers. Keywords: HCV, HBS, ICT and Dental patients.